Epoxy resin composition, semiconductor device and method for manufacturing semiconductor device
Patent Information
- Application Number
- JP2022172413
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-10-27
- Publication Date
- 2025-03-07
AI Technical Summary
Existing epoxy resin compositions used in flip-chip mounting face challenges in maintaining uniform filler distribution due to electrophoresis, leading to reduced connection reliability in semiconductor devices, especially when using metal pillars as electrodes.
An epoxy resin composition incorporating a composite filler with large-diameter particles having small-diameter particles attached to their surfaces is used to suppress uneven filler distribution, enhancing connection reliability by mitigating the effect of potential differences at electrode connections.
The composite filler composition effectively reduces filler segregation and bias in distribution, resulting in improved connection reliability and stability of semiconductor devices.
Smart Images

Figure 00000020_0000
Abstract
Description
[Technical field]
[0001] The present invention relates to an epoxy resin composition, a semiconductor device, and a method for producing a semiconductor device. [Background technology]
[0002] Flip-chip mounting is known as a technique for mounting semiconductor elements to a substrate. Flip-chip mounting is a mounting method that uses a semiconductor element with protruding electrodes (element electrodes) called bumps formed on its surface to directly connect the element electrodes of the semiconductor element to electrodes (substrate electrodes) provided on the surface of a substrate such as a wiring board. In flip-chip mounting, in order to protect the semiconductor element, the substrate connected to the semiconductor element, and the bumps, underfill is filled between the semiconductor element and the substrate and then heated to harden.
[0003] For this underfill, an epoxy resin composition containing an epoxy resin as a main component is mainly used (for example, see Patent Document 1). Meanwhile, the epoxy resin, the semiconductor element, and the substrate each have a different linear expansion coefficient. For this reason, if the stress generated at the electrode connection between the element-side electrode and the substrate-side electrode due to temperature change cannot be absorbed by the sealing material (cured underfill) covering the electrode connection, cracks may occur at the connection. In order to suppress the occurrence of such cracks, in addition to the epoxy resin, the underfill usually also contains a filler made of silica, alumina, or the like, which has a relatively small linear expansion coefficient.
[0004] On the other hand, in recent flip chip mounting, metal pillars such as copper pillars have come to be used instead of bumps as members constituting electrodes from the viewpoint of narrowing pitches. In such flip chip mounting, it is known that in the process of heating and curing the underfill filled to cover the connection part, the separation and aggregation of the filler dispersed evenly in the underfill progresses and the underfill may harden as it is. In such a case, if the filler dispersed in the sealing material (cured underfill) covering the electrode connection part is distributed in a biased state toward the semiconductor element side or the substrate side with respect to the connection interface of the electrode connection part, the connection reliability will decrease. In addition, it is presumed that such separation and aggregation of the filler and the bias in the filler distribution are caused by the electrophoresis of the filler in the underfill filled to surround the electrode connection part due to the potential difference generated by the difference between the material constituting the element side electrode connection surface and the material constituting the substrate side electrode connection surface. For this reason, an epoxy resin composition suitable for suppressing the bias in the filler distribution in the sealing material has been proposed (Patent Document 2). This epoxy resin composition contains, in addition to an epoxy resin and a curing agent, 0.1 to 10 mass% of a first silica filler having an average particle size of 10 nm to 100 nm, 47 to 75 mass% of a second silica filler having an average particle size of 0.3 μm to 2 μm, and 0.1 to 8 mass% of an elastomer, for a total of 50.1 to 77 mass% of the first silica filler and the second silica filler. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-145290 A [Patent Document 2] International Publication No. 2015 / 079708 Summary of the Invention [Problem to be solved by the invention]
[0006] The technology described in Patent Document 2 is useful for improving connection reliability. However, the technology described in Patent Document 2 requires the use of two types of silica fillers having a predetermined particle size and an elastomer in a predetermined amount in order to improve connection reliability, and in this respect, there are certain limitations on the composition design of the epoxy resin composition. Therefore, as with the technology described in Patent Document 2, there is a demand for expanding the options for composition design to improve connection reliability while also making it easier to meet various other needs.
[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an epoxy resin composition having a novel composition capable of suppressing uneven distribution of a filler dispersed in a sealing material (cured product) covering an electrode connection portion, a semiconductor device produced using the same, and a method for producing the semiconductor device. [Means for solving the problem]
[0008] The above object is achieved by the present invention. The epoxy resin composition of the present invention comprises (A) an epoxy resin, (B) at least one component selected from the group consisting of a curing agent and a curing accelerator, and (C) a filler, wherein the (C) filler comprises (C1) a composite filler having large-diameter particles and small-diameter particles adhering to the surfaces of the large-diameter particles.
[0009] In one embodiment of the epoxy resin composition of the present invention, in the (C1) composite filler, the adhesion volume ratio of the small diameter particles to the large diameter particles is preferably 0.05% to 10.0%.
[0010] In another embodiment of the epoxy resin composition of the present invention, in the (C1) composite filler, the adhesion volume ratio of the small diameter particles to the large diameter particles is preferably 0.1% to 5.0%.
[0011] In another embodiment of the epoxy resin composition of the present invention, in the (C1) composite filler, the adhesion area ratio of the small diameter particles to the large diameter particles is preferably 1% to 100%.
[0012] In another embodiment of the epoxy resin composition of the present invention, in the (C1) composite filler, the number of the small diameter particles attached to the large diameter particles is preferably 80,000 or less.
[0013] In another embodiment of the epoxy resin composition of the present invention, in the (C1) composite filler, the particle size ratio of the small diameter particles to the large diameter particles is preferably 0.1% to 50.0%.
[0014] In another embodiment of the epoxy resin composition of the present invention, the small particles constituting the (C1) composite filler preferably have an average particle size of 0.005 μm to 0.12 μm.
[0015] In another embodiment of the epoxy resin composition of the present invention, the large particles constituting the (C1) composite filler preferably have an average particle size of 0.2 μm to 3.0 μm.
[0016] In another embodiment of the epoxy resin composition of the present invention, the content of the (C1) composite filler is preferably 35% by mass to 70% by mass.
[0017] In another embodiment of the epoxy resin composition of the present invention, the (A) epoxy resin preferably contains a liquid epoxy resin.
[0018] In another embodiment of the epoxy resin composition of the present invention, it is preferable that the (A) epoxy resin contains at least one selected from the group consisting of bisphenol F type epoxy resins, bisphenol A type epoxy resins, biphenyl type epoxy resins, aminophenol type epoxy resins, and naphthalene type epoxy resins.
[0019] In another embodiment of the epoxy resin composition of the present invention, the cured product is preferably used as an encapsulant for semiconductor devices.
[0020] The semiconductor device of the present invention comprises a substrate, a semiconductor element disposed on the substrate, and a cured product of the epoxy resin composition of the present invention sealing a gap between the semiconductor element and the substrate.
[0021] The method for manufacturing a semiconductor device of the present invention includes the steps of filling a gap between a substrate and a semiconductor element disposed on the substrate with the epoxy resin composition of the present invention, and curing the epoxy resin composition. Effect of the Invention
[0022] According to the present invention, it is possible to provide an epoxy resin composition having a novel composition capable of suppressing uneven distribution of a filler dispersed in a sealing material (cured product) covering an electrode connection portion, a semiconductor device produced using the same, and a method for producing the semiconductor device. [Brief description of the drawings]
[0023] [Figure 1] 1 is a cross-sectional view showing an example of a cross-sectional structure of a semiconductor device; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] <Epoxy resin composition> The epoxy resin composition of this embodiment includes (A) an epoxy resin, (B) at least one component selected from the group consisting of a curing agent and a curing accelerator, and (C) a filler, and the filler (C) includes (C1) a composite filler having large diameter particles and small diameter particles attached to the surface of the large diameter particles. Therefore, when the epoxy resin composition of this embodiment is used as the epoxy resin composition in the case of filling the gap between an electronic element such as a semiconductor element and a substrate and then curing by heating during flip chip mounting, the uneven distribution of the filler dispersed in the sealing material (cured product) covering the electrode connection part can be suppressed. Therefore, it is easy to obtain a semiconductor device or other electronic device with high connection reliability. Although the details of the reason why such an effect is obtained are unknown, the present inventors presume that it is as follows.
[0025] First, a potential difference occurs at or near the connection interface of the electrode connection part between the element-side electrode and the substrate-side electrode, where the metal material constituting the element-side electrode connection surface and the metal material constituting the substrate-side electrode connection surface are different from each other. For this reason, in a conventional epoxy resin composition that does not use an ionic compound, the filler (large-diameter filler) composed of charged large-diameter particles contained in the epoxy resin composition filled around the electrode connection part is likely to move by electrophoresis to either the semiconductor element side or the substrate side. For this reason, it is considered that the distribution of the large-diameter filler dispersed in the sealing material (cured product) that covers the electrode connection part is likely to become biased.
[0026] However, in the epoxy resin composition of the present embodiment, a composite filler in which small particles are attached to the surface of each large particle constituting the large filler is used as the filler. In such a composite filler, the small particles attached to the surface of the large particles affect and change the charged state of the large particles in some way, so that the composite filler as a whole is less susceptible to the effect of the potential difference at the connection interface of the electrode connection part or in its vicinity, and is less likely to move to either the semiconductor element side or the substrate side. For this reason, it is considered that the uneven distribution of the filler dispersed in the sealing material (cured product) covering the electrode connection part can be suppressed.
[0027] As described above, in flip-chip mounting using metal pillars as electrode members, it is known that the phenomenon of separation and aggregation of fillers contained in the epoxy resin composition and uneven distribution of fillers in the encapsulant occurs. Therefore, the epoxy resin composition of this embodiment is particularly suitable for use as an underfill used in manufacturing semiconductor devices by flip-chip mounting using metal pillars as electrode members. However, if substantially the same phenomenon as described above occurs when manufacturing various electronic devices such as semiconductor devices using conventional general epoxy resin compositions, the epoxy resin composition of this embodiment can of course be used in manufacturing semiconductor devices manufactured by mounting methods other than flip-chip mounting using metal pillars and various electronic devices other than semiconductor devices. Next, the details of each component constituting the epoxy resin composition of this embodiment will be described below.
[0028] (A) Epoxy resin The epoxy resin used in the epoxy resin composition of the present embodiment is not particularly limited as long as it is a variety of epoxy resins generally used for semiconductor encapsulation, but it is preferable to use a liquid epoxy resin from the viewpoint of viscosity and injectability. In addition, as the epoxy resin to be blended in the epoxy resin composition, only one type of epoxy resin may be used, or two or more types of epoxy resins may be used in combination. The number of epoxy groups contained in the epoxy resin (one molecule) may be one or more, but is usually preferably two or more. The upper limit of the number of epoxy groups is not particularly limited, but is usually preferably 5 or less.
[0029] Specific examples of epoxy resins include aliphatic epoxy resins and aromatic epoxy resins, and aromatic epoxy resins are preferred. Examples of aromatic epoxy resins include bisphenol A type epoxy resins such as p-glycidyloxyphenyldimethyltrisbisphenol A diglycidyl ether; bisphenol F type epoxy resins; novolac type epoxy resins; fluorene type epoxy resins; biphenyl aralkyl epoxy resins; diepoxy resins such as p-tert-butylphenyl glycidyl ether and 1,4-phenyldimethanol diglycidyl ether; biphenyl type epoxy resins such as 3,3',5,5'-tetramethyl-4,4'-diglycidyloxybiphenyl; aminophenol type epoxy resins such as diglycidylaniline, diglycidyl toluidine, triglycidyl-p-aminophenol, and tetraglycidyl-m-xylylenediamine; naphthalene type epoxy resins; and epoxy resins having a skeleton derived from plants, but are not limited thereto.
[0030] Among these, bisphenol F type epoxy resins, bisphenol A type epoxy resins, biphenyl type epoxy resins, aminophenol type epoxy resins, and naphthalene type epoxy resins are preferred.
[0031] (B) Hardener and hardening accelerator The curing agent and curing accelerator used in the epoxy resin composition of the present embodiment are not particularly limited as long as they are various commonly used curing agents and curing accelerators. As the (B) component, only the curing agent may be used, only the curing accelerator may be used, or both may be used in combination. When at least the curing agent is used as the (B) component, the blending amount of the curing agent is preferably an amount that provides a stoichiometric equivalent ratio (curing agent equivalent / epoxy group equivalent) with the epoxy resin of 0.6 to 1.5, more preferably an amount that provides a stoichiometric equivalent ratio of 0.7 to 1.2.
[0032] Examples of the curing agent include an amine-based curing agent, an acid anhydride-based curing agent, a phenol-based curing agent, etc. As the curing agent to be blended in the epoxy resin composition, only one type of curing agent may be used, or two or more types of curing agents may be used in combination.
[0033] Specific examples of amine-based curing agents include aliphatic polyamines such as triethylenetetramine, tetraethylenepentamine, m-xylenediamine, trimethylhexamethylenediamine, and 2-methylpentamethylenediamine; alicyclic polyamines such as isophoronediamine, 1,3-bisaminomethylcyclohexane, bis(4-aminocyclohexyl)methane, norbornenediamine, and 1,2-diaminocyclohexane; piperazine-type polyamines such as N-aminoethylpiperazine and 1,4-bis(2-amino-2-methylpropyl)piperazine; and aromatic polyamines such as diethyltoluenediamine, dimethylthiotoluenediamine, 4,4'-diamino-3,3'-diethyldiphenylmethane, bis(methylthio)toluenediamine, diaminodiphenylmethane, m-phenylenediamine, diaminodiphenylsulfone, diethyltoluenediamine, trimethylenebis(4-aminobenzoate), and polytetramethyleneoxide-di-p-aminobenzoate. Other commercially available products include Epicure-W, Epicure-Z (Yuka Shell Epoxy Co., Ltd., product name), jER Cure (registered trademark)-W, jER Cure (registered trademark)-Z (Mitsubishi Chemical Corporation, product name), Kayahard AA, Kayahard AB, Kayahard AS (Nippon Kayaku Co., Ltd., product name), Thothamine HM-205 (Nippon Steel Sumikin Chemical Co., Ltd., product name), Adeka Hardener EH-101 (ADEKA Corporation, product name), Epomic Q-640, Epomic Q-643 (Mitsui Chemicals, Inc., product names), DETDA80 (Lonza, product name), and Thothamine HM-205 (Nippon Steel Sumikin Chemical Co., Ltd., product name).
[0034] Specific examples of acid anhydride curing agents include alkylated tetrahydrophthalic anhydrides such as methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, and methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhimic anhydride, succinic anhydride substituted with an alkenyl group, methylnadic anhydride, and glutaric anhydride.
[0035] Specific examples of phenol-based curing agents include monomers, oligomers, and polymers having a phenolic hydroxyl group in general, such as phenol novolac resins and their alkylated or allylated products, cresol novolac resins, phenol aralkyl (containing a phenylene or biphenylene skeleton) resins, naphthol aralkyl resins, triphenolmethane resins, and dicyclopentadiene-type phenol resins.
[0036] Examples of the curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, and 2-phenyl-4-methylimidazole. Commercially available products include 2-phenyl-4-methylimidazole (product name: 2P4MZ) manufactured by Shikoku Kasei and 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine (product name: 2MZA) manufactured by Shikoku Kasei. The curing accelerator may be used alone or in combination of two or more kinds.
[0037] The amount of the curing accelerator to be added is not particularly limited, but is preferably 0.001 to 20 parts by mass, and more preferably 0.05 to 10 parts by mass, per 100 parts by mass of the epoxy resin.
[0038] (C) Filler In the epoxy resin composition of this embodiment, at least a composite filler (C1) is used as the filler (C). This composite filler has large particles and small particles attached to the surface of the large particles. In other words, the composite filler is a filler composed of particles that are a composite of two types of particles with different particle sizes.
[0039] Such a composite filler cannot be obtained by simply mixing and stirring a small-diameter filler composed of small-diameter particles and a large-diameter filler composed of large-diameter particles together with other components such as epoxy resin during the preparation of an epoxy resin composition. The composite filler is produced by performing a composite treatment in which small-diameter particles are attached to the surfaces of large-diameter particles before the preparation of an epoxy resin composition. The method of such a composite treatment is not particularly limited, but includes a method of mixing and stirring a small-diameter filler and a large-diameter filler. The method of mixing and stirring is not particularly limited, but includes, for example, (1) a method of directly mixing and stirring a small-diameter filler and a large-diameter filler, (2) a method of preparing a suspension in which a small-diameter filler and a large-diameter filler are dispersed and mixed in a suitable solvent, and then volatilizing the solvent from the suspension to obtain a dried product, and further pulverizing the dried product, or (3) a method of granulating a filler by a wet method or a deflagration method, in which the large-diameter particles are granulated, and then the small-diameter particles are granulated and attached to the surfaces of the large-diameter particles. In the process of producing the composite filler, when a mixture of the composite filler and the small diameter filler is obtained, it is preferable to classify this mixture and separate and take out only the composite filler.
[0040] In the above methods (1) and (2), large-diameter fillers and small-diameter fillers that have been surface-treated with a surface treatment agent such as a silane coupling agent can be used. By using a surface treatment agent, it becomes easy to suppress the aggregation of particles and improve the adhesion of small-diameter particles to the surface of large-diameter particles in the process of preparing a composite filler. In addition, when a surface-treated small-diameter filler is used, it becomes easy to attach small-diameter particles to the surface of large-diameter particles while suppressing the aggregation of small-diameter particles. Furthermore, from the same viewpoint, in the above method (3), a surface treatment agent may be used at an appropriate timing in the manufacturing process. In addition, as the surface treatment agent, any surface treatment agent that is used for the surface treatment of conventional fillers can be used without any particular limitation. For example, various silane coupling agents such as methacrylic silane coupling agents, epoxy silane coupling agents, amino silane coupling agents, vinyl silane coupling agents, acrylic silane coupling agents, and mercapto silane coupling agents can be used.
[0041] In the present specification, the term "composite filler" means that the particle size ratio (100 × average particle size of small particles attached to large particles / average particle size of large particles) of the two types of particles constituting the composite filler is 50% or less. However, in practical terms, the particle size ratio is preferably 0.1% to 50%, more preferably 0.2% to 20%, and even more preferably 0.4% to 12%. The average particle size of the large particles constituting the composite filler is preferably 0.1 μm to 10.0 μm, more preferably 0.2 μm to 5.0 μm, and even more preferably 0.2 μm to 3.0 μm. On the other hand, the average particle size of the small particles constituting the composite filler is preferably 0.005 μm to 0.5 μm, more preferably 0.005 μm to 0.12 μm, and even more preferably 0.01 μm to 0.1 μm, on the premise that the particle size ratio is 50% or less. Here, the average particle size D1 (μm) of the large particles constituting the composite filler means the average particle size of 10 large particles observed by a scanning electron microscope (FE-SEM). The average particle size D2 (μm) of the small particles constituting the composite particle means the average particle size of 5 small particles attached to the surface of each large particle that was used to measure the average particle size (i.e., the average particle size of a total of 10 x 5 = 50 particles).
[0042] In the composite filler, the adhesion form is not particularly limited as long as at least one small particle is attached to the surface of the large particle, but the adhesion form is preferably the form described below.
[0043] That is, the adhesion area ratio Rs of small diameter particles to large diameter particles is preferably 1% to 100%, more preferably 2.5% to 100%. The number P of small diameter particles attached to large diameter particles is preferably 80,000 or less, more preferably 50,000 or less. The lower limit of the number of attached particles may be 1 or more, but in practice, 5 or more is preferable, and 10 or more is more preferable. The adhesion volume ratio Rv of small diameter particles to large diameter particles is preferably 0.05% to 10.0%, more preferably 0.1% to 5.0%.
[0044] Here, the adhesion area ratio Rs can be obtained by the following procedure. First, a scanning electron microscope is used to obtain SEM images of 10 large particles contained in the composite filler. Next, the SEM images are corrected and binarized using image analysis software (WinROOF2018, manufactured by Mitani Shoji Co., Ltd.) to obtain an analysis image. Then, in this analysis image, the large particle and the small particle attached to its surface are manually selected, the areas of the large particle and the small particle are calculated, and the area ratio (%) of all small particles attached to the surface of the large particle when the area of the large particle is taken as 100% is obtained. This measurement is performed for 10 large particles, and the average value of the obtained values is obtained as the adhesion area ratio Rs.
[0045] The number of particles P adhering can be calculated by the following procedure. First, the average area s(LP) [μm of each large particle] is calculated from the adhering area ratio Rs and the SEM image used in the calculation, as shown in the following formulas (1) to (3). 2 ], the average area of each small particle s(SP) [μm 2 ], and the total area St(SP) [μm of all small particles attached to the surface of one large particle (however, the observation side of the SEM image) 2 ] is calculated. Equation (1) s(LP) = π × (average particle diameter D1 / 2 of large particles LP) 2 ·Equation (2) s(SP)=π×(average particle diameter D2 / 2 of small diameter particles SP) 2 ·Formula (3) St(SP)=s(LP)×Rs / 100
[0046] Then, the number of attached particles P [pieces] is calculated based on the following formula (4). Equation (4) P = 2 × St(SP) / s(SP) The constant “2” on the right side of equation (4) is a value calculated based on the assumption that the same number of small particles are attached to the surface of the large particles on the back side (unobservable side) opposite the observation surface (front side) of the composite filler shown in the SEM image.
[0047] The deposition volume ratio Rv can be determined by the following procedure. First, the average volume v(LP) [μm of each large particle was calculated from the number of particles P obtained based on the SEM image and equation (4) used to calculate the adhesion area ratio Rs, as shown in the following equations (5) to (7). 3 ], the average volume of individual small particles v(SP) [μm 3 ], and the total volume Vt(SP) [μm 3 ] is calculated. Equation (5) v(LP) = (4 / 3) × π × (average particle diameter D1 / 2 of large-diameter particles LP) 3 ·Formula (6) v(SP)=(4 / 3)×π×(average particle diameter D2 / 2 of small diameter particles SP) 3 Equation (7) Vt(SP) = v(SP) × P
[0048] Then, the deposition volume ratio Rv [%] is calculated based on the following formula (8). Equation (8) Rv = 100 × Vt(SP) / v(LP)
[0049] The material of the large diameter particles constituting the composite filler can be the same as that of the conventionally known inorganic fillers such as silica, alumina, etc. On the other hand, the material of the small diameter filler can be not only the material of the conventionally known inorganic fillers such as silica and alumina, but also the material of the conventionally known organic fillers.
[0050] The content of the composite filler in the epoxy resin composition is not particularly limited, but from the viewpoints of the thermal expansion coefficient of the cured product and the viscosity and injectability of the epoxy resin composition, the content is preferably 30% by mass to 80% by mass, more preferably 35% by mass to 70% by mass, and even more preferably 50% by mass to 70% by mass.
[0051] As the filler (C) to be blended in the epoxy resin composition, the composite filler (C1) alone may be used, or the composite filler (C1) may be used in combination with other fillers (C2). Here, the other fillers may be any fillers commonly used in epoxy resin compositions without any particular restrictions, so long as they are conventionally known fillers that do not have a structure in which small particles are attached to the surface of large particles, as in the composite filler.
[0052] When the composite filler is used in combination with other fillers, the ratio of the composite filler to the total amount of fillers is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, from the viewpoint of suppressing uneven distribution of the filler dispersed in the sealing material (cured product) covering the electrode connection part. Also, the content of the filler contained in the epoxy resin composition is preferably 30% by mass to 80% by mass, more preferably 35% by mass to 70% by mass, and even more preferably 50% by mass to 70% by mass, from the viewpoint of the thermal expansion coefficient of the cured product and the viscosity and injectability of the epoxy resin composition.
[0053] (D) Other ingredients In addition to the components (A) to (C), the epoxy resin composition of the present embodiment may further contain various additives as necessary. The additives are not particularly limited, but may include, for example, core-shell type rubber particles, silane coupling agents, viscosity inhibitors, ion trapping agents, leveling agents, antioxidants, defoamers, flame retardants, colorants, and reactive diluents, and the types and amounts of these additives are the same as in the conventional method. Details of some additives are described below.
[0054] The core-shell type rubber particles used as an additive impart injectability to the epoxy resin composition and suppress peeling and migration of the epoxy resin composition after curing. Examples of rubber particles having a core-shell structure to be masterbatch-treated include rubber particles consisting of a combination of core: polybutadiene and shell: acrylic copolymer, or rubber particles consisting of a combination of core: silicone resin and shell: acrylic copolymer, etc., among which rubber particles consisting of a combination of core: polybutadiene and shell: acrylic copolymer are preferred because they can reduce the shrinkage stress of the epoxy resin composition due to their low elastic modulus within the temperature range in which the epoxy resin composition is used. The masterbatch treatment of rubber particles having a core-shell structure can be performed with a curing agent such as an epoxy resin or an acid anhydride, and epoxy resins, particularly bisphenol-type epoxy resins, are preferred from the viewpoints of storage stability and the presence or absence of adverse effects on humidity. Examples of bisphenol-type epoxy resins include bisphenol A-type epoxy resins and bisphenol F-type epoxy resins, and bisphenol F-type epoxy resins are more preferred.
[0055] The silane coupling agent used as an additive imparts adhesion between the epoxy resin composition and a semiconductor element or a substrate. Commercially available products include, for example, Z-6610, Z-6011, Z-6020, Z-6094, Z-6883, Z-6032, Z-6040, Z-6044, Z-6043, Z-6075, Z-6300, Z-6519, Z-6825, Z-6030, Z-6033, Z-6062, Z-6862, Z-6911, Z-6026, AZ-720, and Z-6050 (all manufactured by Dow Corning Toray Co., Ltd.), KBM-303, KBM-402, KBM-403, KBE-402, KBE-403, KBM-1403, KBM-502, KBM-503, KBE-502, and KBE-50 3, KBM-5103, KBM-602, KBM-603, KBE-603, KBM-903, KBE-903, KBE-9103, KBM-573, KBM-575, KBE-585, KBM-1003, KBE-1003, KBM-802, KBM-803, KBE-846, KBE-9007, X-41-1053, X-41-1056, X-41-1059A, X-41-1805, X-41-1808, X-41-1810, KR-513, X-40-2672B, X-40-9272B, X-40-2651, etc. (all manufactured by Shin-Etsu Chemical Co., Ltd.). The silane coupling agents may be used alone or in combination of two or more kinds.
[0056] The epoxy resin composition of the present embodiment can be prepared by mixing and stirring at least the (A) to (C) components, and in this case, the (D) component can also be added as necessary. The method of mixing and stirring is not particularly limited, and a known mixing and stirring method such as a roll mill can be used. In addition, when the (A) epoxy resin used as a raw material is in a solid state, it is preferable to liquefy it by performing a heat treatment or the like before mixing it with other components, and then mix it. In addition, when preparing the epoxy resin composition, all the raw material components may be mixed at once, or a primary mixture may be prepared by mixing a part of the raw material components selected from all the raw material components, and the remaining components may be mixed with the primary mixture.
[0057] <Uses of epoxy resin composition, semiconductor device and manufacturing method thereof> The epoxy resin composition of the present embodiment can be used as a sealant for various electronic devices such as semiconductor devices, and is particularly suitable for use as a sealant for various electronic devices such as semiconductor devices that have an electrode connection part surrounded by a sealant, and in which the first metal material constituting the electrode connection surface on one side of the connection interface of the electrode connection part is different from the second metal material constituting the electrode connection surface on the other side. Here, the combination of the first metal material and the second metal material is not particularly limited as long as it generates a potential difference when the two are connected, but (a) a combination of a first metal material selected from the group consisting of copper, copper alloy, silver, silver alloy, gold, and gold alloy, and a second metal material selected from the group consisting of tin and tin alloy, and (b) a combination of metal materials that generates a potential difference approximately the same as or greater than the combination of (a) are suitable. When an electronic device having such an electrode connection part is manufactured by resin sealing using the epoxy resin composition of the present embodiment, it is possible to suppress uneven distribution of the filler dispersed in the sealant (cured product) covering the electrode connection part.
[0058] The semiconductor device of this embodiment may include a substrate, a semiconductor element disposed on the substrate, and a sealant (a cured product of the epoxy resin composition of this embodiment) that seals the gap between the semiconductor element and the substrate. The semiconductor device includes an electrode connection portion in which the electrode connection surface of the element-side electrode provided on the semiconductor element is connected to the electrode connection surface of the substrate-side electrode provided on the substrate, and the sealant is disposed so as to surround the electrode connection portion. In the semiconductor device of this embodiment, it is particularly preferable that the element-side metal material constituting the electrode connection surface of the element-side electrode and the substrate-side metal material constituting the electrode connection surface of the substrate-side electrode provided on the substrate are different from each other, and the suitable combination of the two is the same as the suitable combination of the first metal material and the second metal material described above. The element-side electrode and the substrate-side electrode can be formed, for example, of solder bumps or metal pillars, but it is preferable that the element-side electrode is formed of a metal pillar such as a copper pillar.
[0059] The semiconductor device of this embodiment is manufactured by at least a step of filling the gap between the substrate and the semiconductor element disposed on the substrate with the epoxy resin composition of this embodiment (filling step), and a step of curing the epoxy resin composition filled in the gap (curing step). Usually, prior to the filling step, a step of connecting the electrode connection surface of the element side electrode and the electrode connection surface of the substrate side electrode to form an electrode connection part is performed in a state where the surface of the semiconductor element on which the element side electrode is provided faces the surface of the substrate on which the substrate side electrode is provided. Therefore, in the filling step, the epoxy resin composition is filled so as to surround the periphery of the electrode connection part, and the epoxy resin composition surrounding the periphery of the electrode connection part is cured in the curing step (becoming a cured product (sealant)).
[0060] FIG. 1 is a cross-sectional view showing an example of the cross-sectional structure of a semiconductor device, and specifically, an SEM image of the cross-sectional structure near the electrode connection part taken by a scanning electron microscope (FE-SEM) is shown. As shown in FIG. 1, in the vicinity of the electrode connection part 30 consisting of the substrate side electrode 10 and the element side electrode 20 connected to the substrate side electrode 10, a sealant 40, which is a hardened product of the epoxy resin composition filled in the filling step, is arranged so as to surround the electrode connection part 30 (in the figure, the sealant 40 is located between a pair of left and right electrode connection parts 30). In the example shown in FIG. 1, the substrate side electrode 10 is composed of a solder bump made of a tin alloy containing tin as a main component, and the element side electrode 20 is composed of a copper pillar, so that a potential difference occurs when both electrodes 10 and 20 are connected. Also, as shown in FIG. 1, the sealant 40 is composed of a filler (relatively white parts of the sealant 40 in the figure) and a resin matrix (relatively black parts of the sealant 40 in the figure), which is the part other than the filler. The filler and the resin matrix in the encapsulant 40 can be distinguished by specifying an area in the SEM image corresponding to the encapsulant 40 and performing image processing using image processing software. Such image processing is performed by binarizing the area based on the median value of the luminance distribution in the specified area corresponding to the encapsulant 40.
[0061] Meanwhile, the electrode connection part 30 has a connection interface L between the electrode connection surface of the substrate-side electrode 10 and the electrode connection surface of the element-side electrode 20. Here, the region corresponding to the sealing material 40 can be divided into a semiconductor element-side region Ra and a substrate-side region Rb based on an extension line of the connection interface L. In this case, the degree of bias in the distribution of the filler dispersed in the sealing material 40 covering the electrode connection part 30 can be quantitatively evaluated by the filler distribution index shown in the following formula (9). Equation (9) Filler distribution index = 100 × a / b
[0062] Here, in formula (9), a is the filler occupancy rate in the region Ra, and b is the filler occupancy rate in the region Rb. The occupancy rate is a value calculated based on the SEM image obtained by binarization processing as shown in Fig. 1. ImageJ from the National Institutes of Health (NIH) was used for the series of image processing to calculate the filler distribution index.
[0063] When the filler distribution index is 100, it means that the filler dispersed in the encapsulant 40 is distributed most uniformly (the distribution bias is minimal). On the other hand, the filler distribution index is more distant from 100, the filler distribution in the encapsulant 40 is more biased. When the filler distribution index is smaller than 100, it means that the filler is distributed biased toward the region Rb, and when it is larger than 100, it means that the filler is distributed biased toward the region Ra. The filler tends to be distributed biased toward either the region Ra or the region Rb, depending on the combination of the metal material constituting the electrode connection surface of the substrate-side electrode 10 and the metal material constituting the electrode connection surface of the element-side electrode 20. In the semiconductor device of this embodiment, the filler distribution index is preferably within the range of 100±60, more preferably within the range of 100±50, and even more preferably within the range of 100±40. EXAMPLES
[0064] Specific examples of the present invention will be described below with reference to examples, but the present invention is not limited to the examples described below.
[0065] 1. Raw material components used in the preparation of the epoxy resin composition The components listed below were used to prepare the epoxy resin compositions of the Examples and Comparative Examples.
[0066] (A) Epoxy resin a1: YDF8170 (bisphenol F type, epoxy equivalent 158g / eq, number of epoxy groups: 2, manufactured by Nippon Steel Chemical & Material Co., Ltd.) a2: EXA-850CRP (bisphenol A type, epoxy equivalent 172g / eq, number of epoxy groups: 2, manufactured by DIC) a3: HP4032D (naphthalene type, epoxy equivalent 140g / eq, number of epoxy groups: 2, manufactured by DIC) a4: jER630 (aminophenol type, epoxy equivalent 98g / eq, number of epoxy groups: 3, manufactured by Mitsubishi Chemical Corporation) a5: YX7400 (biphenyl type, epoxy equivalent 440g / eq, number of epoxy groups: 2, manufactured by Mitsubishi Chemical Corporation)
[0067] (B) Hardener and hardening accelerator b1: HDAA (amine-based hardener, 4,4'-diamino-3,3'-diethyldiphenylmethane, active hydrogen equivalent 63.5g / eq, manufactured by Nippon Kayaku Co., Ltd.) b2: Ethacure 100 (amine-based hardener, diethyltrienediamine, active hydrogen equivalent 44.6g / eq, manufactured by Albemarle) b3: HN5500 (anhydrous acid, active hydrogen equivalent 168g / eq, manufactured by Hitachi Chemical Co., Ltd.) b4: MEH8005 (phenolic hardener, active hydrogen equivalent 135g / eq, manufactured by Meiwa Kasei Co., Ltd.) b5: 2P4MZ (2-phenyl-4-methylimidazole, manufactured by Shikoku Chemical Industry Co., Ltd.)
[0068] (C) Filler (C1) Composite filler The composite fillers used in the preparation of the epoxy resin composition are c1-2 to c1-13 shown below. The preparation methods of these composite fillers will be described later. c1-2 (average particle size of large particles: 0.6 μm, average particle size of small particles: 0.01 μm, material of small and large particles: silica) c1-3 (average particle size of large particles: 0.6 μm, average particle size of small particles: 0.01 μm, material of small and large particles: silica) c1-4 (average particle size of large particles: 0.6 μm, average particle size of small particles: 0.01 μm, material of small and large particles: silica) c1-5 (average particle size of large particles: 0.6 μm, average particle size of small particles: 0.01 μm, material of small and large particles: silica) c1-6 (average particle size of large particles: 0.6 μm, average particle size of small particles: 0.01 μm, material of small and large particles: silica) c1-7 (average particle size of large particles: 0.6 μm, average particle size of small particles: 0.01 μm, material of small and large particles: silica) c1-8 (average particle size of large particles: 0.6 μm, average particle size of small particles: 0.05 μm, material of small and large particles: silica) c1-9 (average particle size of large particles: 0.3 μm, average particle size of small particles: 0.01 μm, material of small and large particles: silica) c1-10 (average particle size of large particles: 1.0 μm, average particle size of small particles: 0.01 μm, material of small and large particles: silica) c1-11 (average particle size of large particles: 1.0 μm, average particle size of small particles: 0.01 μm, material of small and large particles: silica) c1-12 (average particle size of large particles: 0.6 μm, average particle size of small particles: 0.01 μm, material of small and large particles: silica) c1-13 (average particle size of large particles: 0.6 μm, average particle size of small particles: 0.01 μm, material of small and large particles: silica)
[0069] (C2) Other fillers c2-1: Silica filler (average particle size: 0.6 μm, no surface treatment)
[0070] (D) Other ingredients d1: MX-137 (core-shell type butadiene rubber particles, manufactured by Kaneka Corporation) d2: MX-965 (core-shell type silicone rubber particles, manufactured by Kaneka Corporation) d3: KBM403 (3-glycidoxypropyltrimethoxysilane, coupling agent, manufactured by Shin-Etsu Chemical Co., Ltd.) d4: CG1400 (dicyandiamide, manufactured by Air Products and Chemicals) d5: TPP (triphenylphosphine, viscosity suppressant, manufactured by Hokko Chemical Industry Co., Ltd.)
[0071] 2. Preparation of Composite Fillers The large-diameter filler and the small-diameter filler were thoroughly mixed and stirred using a mixer according to the composition shown in Table 1. As shown in Table 1, the large-diameter filler was a filler that had been surface-treated with a silane coupling agent or a filler that had not been surface-treated, and the small-diameter filler was a filler that had been treated with a silane coupling agent. The resulting stirred mixture was then classified to remove the small-diameter filler from the stirred mixture, and the classified products were used as composite fillers c1-2 to c1-13. When the particles contained in the classified products were examined with a scanning electron microscope, it was confirmed that all of the particles observed had a structure in which small-diameter particles were attached to the surface of large-diameter particles.
[0072] [Table 1]
[0073] 3. Preparation of Epoxy Resin Composition The epoxy resin compositions of Examples 1 to 26 and Comparative Example 1 were prepared by mixing and stirring the raw materials using a roll mill so that the components (A) to (D) had the blending ratios (parts by mass) shown in Tables 2 to 4.
[0074] 4. Evaluation Results The properties of the composite filler used in the preparation of the epoxy resin composition of each Example, as well as the viscosity, thixotropy index (TI), injectability and filler distribution index of the epoxy resin composition of each Example and Comparative Example, were measured or evaluated according to the procedures shown below. The results are shown in Tables 2 to 4.
[0075] 4.1 Properties of composite fillers (1) Particle size ratio The particle size ratio of the two types of particles that make up the composite filler (100 × average particle size of small particles attached to large particles / average particle size of large particles) was determined using a scanning electron microscope according to the following procedure. First, the particle sizes of 10 large particles contained in the composite filler were measured to determine their average particle size. Next, the particle sizes of 5 small particles attached to the surface of each of the large particles that were the subject of measurement were measured to determine their average particle size (i.e., the average particle size of a total of 10 × 5 = 50 small particles). The particle size ratio was then calculated based on the average particle sizes of these two types of particles.
[0076] (2) Adhesion area ratio Rs The adhesion area ratio Rs was obtained by the following procedure. First, a scanning electron microscope was used to obtain SEM images of 10 large particles contained in the composite filler. Next, the SEM images were corrected and binarized using image analysis software (WinROOF2018, manufactured by Mitani Shoji Co., Ltd.) to obtain an analysis image. In this analysis image, the large particles and the small particles adhering to their surfaces were manually selected, the areas of the large particles and the small particles were calculated, and the area ratio (%) of all small particles adhering to the large particle surface when the area of the large particles was set to 100% was obtained. At this time, this measurement was performed for 10 large particles. The average value of the obtained values was obtained as the adhesion area ratio Rs. When using the image analysis software, the image analysis was performed under the following conditions. Calibration: Manual calibration Filter: Median filter 3x3
[0077] (3) Number of particles P The number of attached particles P was calculated based on the above-mentioned formula (4).
[0078] (4) Deposition volume ratio Rv The number of adhered particles Rv was calculated based on the above-mentioned formula (8).
[0079] 4.2 Viscosity, injectability, thixotropy index (TI) and filler distribution index (1) Viscosity The viscosity of the epoxy resin composition immediately after preparation was measured using a Brookfield rotational viscometer HBDV-1 (using spindle SC4-14) under conditions of a liquid temperature of 25° C. and 50 rpm, and a liquid temperature of 25° C. and 5 rpm.
[0080] (2) Thixotropy index (TI) The thixotropy index (TI) of the epoxy resin composition was calculated as the ratio of the viscosity measured at 5 rpm to the viscosity measured at 50 rpm using the two types of viscosities obtained in the above-mentioned viscosity measurement.
[0081] (3) Injectability A test piece was prepared by providing a gap of 20 μm or 50 μm on an organic substrate (FR-4 substrate) and fixing a glass plate instead of a semiconductor element. Next, the test piece was placed on a hot plate set at a temperature of 110° C., and an epoxy resin composition was applied to one end of the glass plate, thereby injecting the epoxy resin composition into the gap formed between the organic substrate and the glass plate. At this time, the time until the injection distance of the epoxy resin composition reached 20 mm was measured when the end of the glass plate to which the epoxy resin composition was applied was set at 0 mm. This procedure was carried out twice, and the average value of the two measured values was calculated as the injection time (seconds).
[0082] (4) Filler distribution index A semiconductor device was fabricated by flip-chip mounting using an epoxy resin composition. Here, the semiconductor device was fabricated using a substrate having a substrate-side electrode 10 made of a tin alloy containing tin as a main component, and a semiconductor element having an element-side electrode 20 made of a copper pillar. The semiconductor device was fabricated by sequentially carrying out a connection process, a filling process, and a curing process. The curing conditions in the curing process were 150°C and 120 minutes.
[0083] Next, the semiconductor device with a chip size of 10 mm x 10 mm was cut using a slicer (ISOMET 4000, manufactured by BUEHLER), and the cut surface was polished using abrasive paper of No. 240, No. 800, and No. 1200 in order to obtain a sample for SEM observation in which the cut surface of the center of the semiconductor device was exposed. Then, the cut surface of the sample for SEM observation was imaged using FE-SEM to obtain an SEM image of an enlarged view of the vicinity of the electrode connection part 30 as illustrated in FIG. 1, and the filler occupancy rate a in the region Ra and the filler occupancy rate b in the region Rb were obtained by performing image processing based on this SEM image using the procedure described above. Next, these values a and b were substituted into formula (9) to calculate the filler distribution index. The filler distribution index was judged to be good when it was within 100±60.
[0084] [Table 2]
[0085] [Table 3]
[0086] [Table 4] [Explanation of symbols]
[0087] 10 Substrate side electrode 20 Element side electrode 30 Electrode connection part 40 Encapsulating material
Claims
1. (A) an epoxy resin; (B) at least one component selected from the group consisting of a curing agent and a curing accelerator; (C) a filler, The epoxy resin composition, wherein the filler (C) comprises a composite filler (C1) having large-diameter particles and small-diameter particles attached to the surfaces of the large-diameter particles.
2. 2. The epoxy resin composition according to claim 1, wherein in the (C1) composite filler, the adhesion volume ratio of the small diameter particles to the large diameter particles is 0.05% to 10.0%.
3. 3. The epoxy resin composition according to claim 1, wherein in the (C1) composite filler, the adhesion volume ratio of the small diameter particles to the large diameter particles is 0.1% to 5.0%.
4. 3. The epoxy resin composition according to claim 1, wherein in the (C1) composite filler, the adhesion area ratio of the small diameter particles to the large diameter particles is 1% to 100%.
5. 3. The epoxy resin composition according to claim 1, wherein in the (C1) composite filler, the number of the small diameter particles attached to the large diameter particles is 80,000 or less.
6. 3. The epoxy resin composition according to claim 1, wherein in the (C1) composite filler, a particle size ratio of the small diameter particles to the large diameter particles is 0.1% to 50.0%.
7. 3. The epoxy resin composition according to claim 1, wherein the small particles constituting the (C1) composite filler have an average particle size of 0.005 μm to 0.12 μm.
8. 3. The epoxy resin composition according to claim 1, wherein the average particle size of the large particles constituting the (C1) composite filler is 0.2 μm to 3.0 μm.
9. The epoxy resin composition according to claim 1 or 2, wherein the content of the (C1) composite filler is 35% by mass to 70% by mass.
10. 3. The epoxy resin composition according to claim 1, wherein the epoxy resin (A) comprises a liquid epoxy resin.
11. 3. The epoxy resin composition according to claim 1, wherein the epoxy resin (A) comprises at least one selected from the group consisting of bisphenol F type epoxy resins, bisphenol A type epoxy resins, biphenyl type epoxy resins, aminophenol type epoxy resins, and naphthalene type epoxy resins.
12. 3. The epoxy resin composition according to claim 1, wherein the cured product is used as an encapsulant for semiconductor devices.
13. A substrate; A semiconductor element disposed on the substrate; A cured product of the epoxy resin composition according to claim 1 or 2, which seals a gap between the semiconductor element and the substrate; A semiconductor device comprising:
14. A step of filling a gap between a substrate and a semiconductor element disposed on the substrate with the epoxy resin composition according to claim 1 or 2; curing the epoxy resin composition; A method for manufacturing a semiconductor device comprising the steps of: